A Biblical Reflection on Truth and Justice "Born from the Heart of the Church" (Ex corde Ecclesiae) - Prof. Michael Ufok Udoekpo (Pharos Journal of Theology, 2025)
In August 1990, Pope John Paul II issued the Apostolic Constitution, Ex corde Ecclesiae (born from the heart of the Church), on the identity and norms governing Catholic universities. Article 4 of the introductory section of that document stresses the honour and responsibility of a Catholic University, including those in Africa, to consecrate itself without reserve to the cause of truth. his truth contains the meaning of nature, mankind and God, and all of their relationships. It anchors freedom, the role of religious faith, the dignity of every human person, cultural dialogue and justice. Echoes of Ex corde Ecclesiae and related ecclesiastical documents that serve as instruments of truth and justice are heard and amplified in the 2018 Apostolic Constitution, Veritatis Gaudium (the joy of truth) of Pope Francis. In the light of these documents and rooted in sacred scriptures, this article discusses some long standing socio-political, economic, religious, ethical and cultural challenges and elements of falsehood and injustices confronting Africa and her institutions. In attempting to offer remedies to these challenges, this work engages in a biblical, contextual and theological reflection on the notions of truth (ʾǝmet, alētheia) and justice (mišpāṭ, dikaiosynē). It aims at fostering and inspiring God's saving hope that does not disappoint (Rom 5:5; 8:24), among readers in Nigeria, as well as promote growth in the mission of the Church in Africa and beyond.